Treating young adults with type 2 diabetes or monogenic diabetes - Owen, K (Elsevier, 2016)
It is increasingly recognised that diabetes in young adults has a wide differential diagnosis. There are many monogenic causes, including monogenic beta-cell dysfunction, mitochondrial diabetes and severe insulin resistance. Type 2 diabetes in the young is becoming more prevalent, particularly after adolescence. It's important to understand the clinical features and diagnostic tools available to classify the different forms of young adult diabetes. Classic type 1 diabetes is characterised by positive β-cell antibodies and absence of endogenous insulin secretion. Young type 2 diabetes is accompanied by metabolic syndrome with obesity, hypertension and dyslipidaemia. Monogenic β-cell dysfunction is characterised by non-autoimmune, C-peptide positive diabetes with a strong family history, while mitochondrial diabetes features deafness and other neurological involvement. Severe insulin resistance involves a young-onset metabolic syndrome often with a disproportionately low BMI. A suspected diagnosis of monogenic diabetes is confirmed with genetic testing, which is widely available in specialist centres across the world. Treatment of young adult diabetes is similarly diverse. Mutations in the transcription factors HNF1A and HNF4A and in the β-cell potassium ATP channel components cause diabetes which responds to low dose and high dose sulfonylurea agents, respectively, while glucokinase mutations require no treatment. Monogenic insulin resistance and young-onset type 2 diabetes are both challenging to treat, but first line management involves insulin sensitisers and aggressive management of cardiovascular risk. Outcomes are poor in young-onset type 2 diabetes compared to both older onset type 2 and type 1 diabetes diagnosed at a similar age. The evidence base for treatments in monogenic and young-onset type 2 diabetes relies on studies of moderate quality at best and largely on extrapolation from work conducted in older type 2 diabetes subjects. Better quality, larger studies, particularly of newer agents would improve treatment prospects for young adults with diabetes.